Quality of Life after Functional Endoscopic Sinus Surgery - Mishra, DK; Bhatta, R; Verma, LR (Nepalese Journal of ENT Head and Neck Surgery, 2011)
Key words: Chronic sinusitis; sinus surgery; outcome DOI: 10.3126/njenthns.v1i2.4754 Nepalese J ENT Head Neck Surg Vol.1 No.2 (2010) p.6-8